EFEKTIVITAS BATAS USIA NIKAH MENURUT UNDANG-UNDANG NOMOR 16 TAHUN 2019 DI LAMPUNG TIMUR - Alif Aradia Yulia (Syakhsiyah Jurnal Hukum Keluarga Islam, 2021)
Marriage is a bond between a female guardian (prospective wife) and a male (prospective husband) which is carried out in the presence of two witnesses who meet the requirements. Maturity of age is important to form a prosperous family without ending in divorce. So the government sets the age limit for marriage in Law No. 1 of 1974 whose application creates discrimination, then Article 7 which regulates the age limit for marriage in the Law is changed to Law No. 16 of 2019. This writing aims to determine the effectiveness of the age limit for marriage according to Law No 16 of 2019 in East Lampung, based on data obtained from the case tracking information system at the Sukadana religious court, East Lampung, it turns out that there are still many applications for marriage dispensation, almost 80% of which are granted. This article uses interview and documentation methods. The type of research used is descriptive quantitative research and qualitative research using data from the Sukadana Religious Court SIPP, this article is in the form of the number of applications for marriage dispensation which is expected to provide an overview through the calculation of the data obtained regarding the effectiveness of the marriage age limit in Law No. 16 of 2019 in East Lampung. Based on the results found, it turns out that the application of the Marriage Age Limit in Law No. 16 of 2019 has not been effectively implemented in East Lampung, especially at the Sukadana Religious Court, seen from the large number of marriage applications that have been granted.